Slaging Analysis Based on Boiler Wall Temperature at PLTU Paiton Unit 3 - Muhammad Hasan Basri; Tijaniyah Tijaniyah; Risto Moyo (Universitas Ahmad Dahlan, 2023)
Slagging on boiler surfaces in power plants is still a serious problem to reduce thermodynamic efficiency and threaten the operation of generating units. In this study, an innovative slagging diagnosis method based on analysis of vibration signals from tube panels is proposed to monitor slagging conditions. We analyze boiler wall temperature under various slagging conditions and air velocity at PLTU Paiton unit 3. Root Mean Square (RMS) in the time domain and decomposition in the frequency domain are used to extract features from vibration signals and predict slagging conditions without turning them off in the future. It was found that the RMS value of the tube panel signal decreased with increasing slagging weight, especially at low air speeds. The relative signal energy at a certain frequency will experience significant changes. In order to verify the experimental results on changes in the tube panel vibration signal features under various slagging conditions, we have successfully demonstrated our laboratory results through analysis of the tube panel vibration signal. This indicates that the vibration signal of the tube panel between the heater and the furnace wall panel can be collected and used for the diagnosis of slagging in the walls of a coal boiler. Our study is promising for the prediction of slagging and further mitigating the risk caused by slagging of exchange panels in boilers